Penerapan metode moto-kinesthetic dalam meningkatkan kemampuan artikulasi konsonan apico-alveolar /-n/ pada anak dengan gangguan artikulasi fungsional - Yosrika; Fazria Triadiarini Putri; Euis Reliyanti Arum (JURNAL TERAS KESEHATAN, 2025)
Functional articulation disorder refers to difficulty in pronouncing speech sounds without any organic abnormalities in the structure or function of the speech organs. This study aims to evaluate the application and effectiveness of the moto-kinesthetic method in improving the articulation of the apicoalveolar consonant /n/ in a 5-year-old child with functional articulation disorder. The research method was a case study  with purposive sampling technique. Data were collected through interviews with the patient’s family, direct observation, as well as pre-test and post-test assessments to determine diagnosis, prognosis, and appropriate intervention strategies. The intervention consisted of ten therapy sessions using the moto-kinesthetic approach, which focuses on physical manipulation of the speech organs to support accurate articulation. Results showed an improvement in the child's articulation ability from the score of 0 to 4, representing a therapy success rate of 80%. These findings indicate that the moto-kinesthetic method is effective for treating articulation disorders, particularly in the pronunciation of the /-n/ sound, and may serve as a viable intervention strategy in clinical speech therapy practice.